Thermophysical properties of materials for nuclear engineering: A tutorial and collection of data. - International Atomic Energy Agency (nternational Atomic Energy Agency, 2013)
A resource for reactor physicists and engineers and students of nuclear power engineering, this publication provides a comprehensive summary of the thermophysical properties data needed in nuclear power engineering. It includes data for nuclear fuels (metallic and ceramic), coolants (gases, light water, heavy water and liquid metals), moderators, absorbers and structural materials. The correlations and equations provided allow for the estimation of all important thermodynamic and transport properties. The detailed material properties of both solid and liquid states are shown in tabular form. The data on thermophysical properties of saturated vapors of some metals are also given.--Publisher's description